Effect of thickness on impact resistance of lightweight aggregate concrete - Yahaghi J.; Kamal N.L.B.M.; Muda Z.C.; Shafigh P.; Beddu S.B. (Research India Publications, 2023)
This paper explore the impact resistance of lightweight aggregate concrete from the results of an experimental study. The lightweight aggregate used in this study was oil palm shell, which is an agricultural solid waste, origin from palm oil industry. Oil palm shell (OPS) is a main solid pollutant of the environment and can be used as a replacement for the conventional aggregate in lightweight concrete. A self-fabricated drop-weight impact test rig was used to simulate a low-velocity projectile impact on the slab specimens. Different thickness of 20, 30 and 40 mm were tested for impact resistance on specimens. The outcome demonstrate that increasing the thickness improves the impact resistance significantly, but the effect is more pronounced for ultimate failure crack resistance than the first crack resistance. Research India Publications.